WEBINAR AS A VARIETY OF WEB E-CONFERENCE AND ITS PLACE IN A NETWORKED COLLABORATIVE LEARNING PROCESS (Journal of Information Technologies in Education (ITE), 2014)
This article investigates the possibility of using didactic webinars for implementing educational and scientific activities of highly qualified personnel. Substantiated scientific - theoretical foundations of the webinar and discussed its advantages over classical seminar.Discovered practical problems that need solving during implementation webinars and electronic conferences.
Keywords: webinar; e-conference; online; distance learning; collaborative learning